Perbandingan Kinerja Keuangan Sebelum dan Sesudah Emisi Obligasi - Kusnadi Kusnadi; Eka Sari Ningsih (Universitas Malahayati, 2014)
This study aims to provide empirical evidence whether there are differences in the manufacturing company's financial performance before and after bond issuance as measured by the method of financial ratios. The hypothesis in this study is whether or not there is a difference in the company's financial performance before and after the bond issuance. The hypothesis was tested with different test Pired Sample Test through software SPSS.versi 17 with a confidence level of 9.5%. The sample used in this study is a manufacturing company that has gone public on the Indonesian Stock Exchange until December 31, 2013 and conduct bond emissions between the years 2001-2012. Observation period is three years before and three years after emission. Based on predetermined criteria then we obtain the final sample of 13 companies that do bond issuance. The results of testing the company's financial ratios for a period of three years before and three years after bond issuance showed significant value so it can be concluded there is no difference between the manufacturing company's financial performance before and after the bond issuance